INVASIVE SPECIES FLOW INTO THE GLOBAL SUPPLY CHAIN - Eslava Sarmiento, Alexander
The management of the phytosanitary risk associated with each piece of Wood Packaging Material (WEM) and in the wooden pallets that flow in the Global Supply Chain (CSG) is a complex process that involves multiple entities and countries. The ISPM 15 Certification Mark must indicate full compliance with the treatment, reducing the need for high-frequency inspections and reducing the need for additional documentation such as the phytosanitary certificate. However, the volume of international trade continues to increase each year with tens of millions of shipments having WEM and wooden pallets associated with the goods, indicating that WEM presents a very high real risk of introducing invasive species into the CGS. The data collection of the WEM and the wooden pallets flowing in the CGS could improve with the support of the disruptive technology of Blockchain, recording the number of infested units within the shipments, specifying when bark is present, if the residual pieces are larger than the current tolerance limits and the specified treatment type. This information would allow a clear assessment of the actual risk of individual infested consignments in the CGS.